Al/NiO nanocomposites for enhanced energetic properties: Preparation by polymer assembly method. (5th December 2019) - Dong, Haoxue; Xia, Min; Wang, Cuixiao; Li, Guoping; Luo, Yunjun
Abstract: Al/NiO nanocomposites are prepared via co -assembly with poly(4-vinylpyridine) (P4VP), and their enhanced energetic properties and combustion performance are studied. The results show that compared with physical mixing method, the structure of the Al/NiO nanocomposites with P4VP is more regular and compact, in which the grain sizes of Al and NiO nanoparticles are reduced from 56 nm and 29 nm to 51 nm and 25 nm, respectively. Therefore, their heat release, the maximum pressure of combustion, pressure rise rate of combustion and the maximum burning rate are greatly enhanced to 2190 J/g, 0.35 MPa, 260 MPa/s and 462 m/s, respectively, better than those obtained by physical mixing method. We further revealed that the reason for these improvements is that our method effectively suppresses the aggregation of nanoparticles, leading to uniform contact and sufficient interfacial area between the oxidant (NiO) and nano-fuel (Al), and thus significantly improving the reaction efficiency. Graphical abstract: Unlabelled Image Highlights: Al/NiO nanocomposites were prepared via co-assembly with poly(4-vinyl pyridine). Poly(4-vinyl pyridine) performed the "bridge" effect in the co-assembly process. Al/NiO nanocomposites prepared with poly(4-vinyl pyridine) had better thermal performance.